Estudo, trabalho e agroecologia apontamentos sobre a formação técnica do MST (PR) - Pires, João Henrique Souza (Editora Oficina Universitária, 2021)
João Henrique Souza Pires' book is the result of a rich combination of his studies in the master's degree in education, at the São Paulo State University, and his militancy trajectory within the Landless Rural Workers Movement (MST). Readers will find, here, an analysis of practices for training technicians in agroecology developed in centers/schools controlled by the MST. Specifically, the pedagogical and methodological practices of the 2nd technical course in agroecology integrated into high school, held at Escola José Gomes da Silva (Paraná). The context in which the analysis is carried out should also be highlighted, as it refers to a change that occurs in the attempt to overcome the dominant matrix on the agrarian question in Brazil, built since the period of the Civil-Military Dictatorship under the infamous "revolution". green". As a counterpoint to this conservative matrix, Pires' study has as its structuring axis what he calls the "transition" to agroecology, whose conceptions and history in Brazil are analyzed. Within the scope of the MST's educational activities, the relevance of this transition finds a decisive moment in the analysis of the construction of the Centers/Schools of Agroecology in Paraná. It can be said, therefore, that one of the main contributions of this book lies in the way it helps us to understand the reasons why the transition to the agroecological matrix and the autonomous educational activities of the MST form a single and the same process, even if this not be hegemonic within the movement. The profound contradictions that have been marking the advance of "agribusiness" in the Brazilian countryside, inexorably accompanied by destructive advances on the still existing and relatively preserved ecosystems, make it redundant to talk about the relevance of these themes. May reading the book be, therefore, an invitation to engage in the struggles of our time, in all fields, but especially in this one that emerges from the fusion between agroecology and education.